Argulus (Fish Louse) Infections in Fish - Natalie Steckler; Roy P. Yanong (EDIS)
Argulus species (Family: Argulidae), more commonly known as fish lice, are members of a large group of branchiuran parasites that infest and cause disease in fish. The argulids are crustaceans and are related to crabs, lobsters, and shrimp. This 5-page fact sheet was written by Natalie Steckler and Roy P. E. Yanong and published by the UF Department of Fisheries and Aquatic Sciences, November 2012.